(untitled) (Journal of Economic Research & Business Administration, 2015)
The article examines the processes of integration in the post-Soviet space, in particular the processes of integration of Kazakhstan into the world economy. Kazakhstan is an active participant in the integration process tends to several major national markets, which requires the provision of economic security. At the present stage, the economic development of countries is provided by the transition to an innovative type of development that contributes to the intensification of economic cooperation between the countries. There are a number of prerequisites for cooperation, including the available scientific and technical potential of each state, a well-developed system of research centers and institutes, the accumulated professional and academic contacts, established ways of international cooperation. However, the article analyzes the impact of economic integration and growth of innovation in economic development. Examines the current geopolitical trends in the world economy: a strategy for the development of foreign economic relations of Russia, Kazakhstan and Belarus.